Pipeline modelling for leak detection using pressure gradient method - Nik Ahmad Ridzlan, Nik Aiemen Razieq (IRC, 2016)
Pipelines are used in many industries to convey fluids over long distances. They are reliable and economical means to transport fluids. However, they will deteriorate over time due to corrosion, mechanical stresses or improper pipeline use which can lead to leaks. Depending on the nature liquid, leaks lead to higher operating cost, pollution, and endangerment to life. Although many methods are already developed, the leak detection regime can be challenging to implement as they need many instrumentations to be installed for them to be accurate.